1998
DOI: 10.1021/bi972377w
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Nicked and Gapped DNA Structures by NMR and Molecular Dynamic Simulations in Water

Abstract: We have analyzed and compared the molecular structures and dynamics of DNA duplexes containing a nick or a gap of one nucleotide where the base in front of the gap is a guanine. The continuous strand has the sequence 5'(CAGAGTCXCTGGCTC) where the residue X is absent for the nick, 14-mer, and where it is a G residue for the gap. Duplexes were formed with the two corresponding 7-mers. Neither of these is phosphorylated adjacent at the nick site, but it is a good model for a single strand break. For the nick stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
71
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 48 publications
15
71
0
Order By: Relevance
“…This challenge can be addressed by a combination of experimental approaches and molecular dynamics simulations. In recent years, a significant number of molecular dynamics studies [23][24][25][26][27][28][29][30] on DNA and RNA systems have appeared. Cheatham & Kollman reviewed molecular dynamics simulations of nucleic acids from 1995 to 2000, discussing force fields for nucleic acids and simulation protocols using explicit solvent and counterions.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge can be addressed by a combination of experimental approaches and molecular dynamics simulations. In recent years, a significant number of molecular dynamics studies [23][24][25][26][27][28][29][30] on DNA and RNA systems have appeared. Cheatham & Kollman reviewed molecular dynamics simulations of nucleic acids from 1995 to 2000, discussing force fields for nucleic acids and simulation protocols using explicit solvent and counterions.…”
Section: Introductionmentioning
confidence: 99%
“…On the experimental side, Protozanova et al have measured free energy of stacking for base-pair steps in a nicked DNA duplex (Protozanova et al 2004). It is attractive to generalise these stacking-free energies for nicked DNA to the intact DNA double helix; however, NMR analyses have shown that the broken phosphodiester bond pushes the conformation away from canonical B-form (Pieters et al 1989;Roll et al 1998; Snowden-Ifft & Wemmer, 1990) which leaves . Overall then, while there is significant disagreement on the magnitude (and sometimes the ranking) of the 10 stacking energies for complementary base-pair steps, the key feature of a weak CG stack which points to the existence of a GNC triplet code is preserved.…”
Section: −1mentioning
confidence: 99%
“…The convolution in (8) is a convolution defined on SE(3). Letting g and h denote any group elements in SE(3), and letting f a (g) and f b (g) be two arbitrary functions defined on SE(3), the convolution on SE(3) is defined as 51 (10) where the little circle is the group multiplication operator for rigid-body motions. Equation (8) can be extended further to solve the multi-joint case by convolving more PDFs of involved segments and joints.…”
Section: General Ideamentioning
confidence: 99%
“…The bending angle caused by a single gap was estimated at around 12°. Roll et al reported a fluctuating bending angle centered around 17° at the nick site of DNA based on nuclear magnetic resonance (NMR) experiments and molecular dynamics (MD) simulations 10 . Kahn et al studied the bending and flexibility induced by symmetric internal loops by gel electrophoresis experiments and cyclization kinetics analysis, and found that the internal loop induced high local isotropic flexibility 11 .…”
Section: Introductionmentioning
confidence: 99%